Prenatal diagnosis of congenital heart disease in the northern region of England: benefits of a training programme for obstetric ultrasonographers. Issue 3 (1st September 2000) - Hunter, S; Heads, A; Wyllie, J; Robson, S
Abstract : OBJECTIVE: To examine the results of fetal cardiac scanning and audit the changes in performance resulting from the introduction of a training programme for obstetric ultrasonographers. METHODS: Using the database of the Northern Regional Congenital Abnormality Survey (NORCAS), fetuses with complex or significant congenital heart disease (CCHD) diagnosed prenatally in 1994 were identified. A simple programme of centralised and local training was instituted in 1995 by the department of paediatric cardiology to teach obstetric ultrasonographers in district general hospital maternity departments to identify congenital heart malformations. The results of the training programme were assessed by comparing the 1994 identification rate of CCHD with the rates for 1996 and 1997. RESULTS: Birth rate fell during the study from 35 026 in 1994 to 32 874 in 1997. Registration of CCHD also fell, from 115 in 1994 to 87 in 1997. Prenatal recognition of CCHD rose from 17% in 1994 to 30% in 1995 and 36% in 1996. In 1997 it fell slightly to 26.9%. The total number of scans did not change much year on year, but the number of parents choosing termination increased significantly (from 22.7% to 57%). CONCLUSIONS: A simple training programme for obstetric ultrasonographers increased their ability to detect serious congenital heart disease at a routine 18–20 week anomaly scan. With a termination rate of more than 50%, the incidence of CCHD in the population fell from 3.3/1000 to 2.6/1000 live births. This audit, conducted within a stable population using ascertainment by a well established fetal malformation registry, suggests that prenatal diagnosis may have a significant effect on the incidence of complex or serious congenital cardiac malformations.